Synthesis, Growth and Spectral Studies of Cadmium Mercury Thiocyanate Dimethyl Sulfoxide: An Efficient Non-linear Optical Single Crystal - Christian Prasana, Johanan; Anuradha, A.; Madhavan, J.; Sagayaraj, P. (Asian Journal of Chemistry, 2012)
The salt of tetrathiocyanato cadmium(II) mercury(II)-dimethyl sulfoxide was synthesized by using dimethyl sulfoxide as ligand to react with cadmium mercury tetrathiocyanate (CMTC) in a mixture of dimethylsulfoxide and double distilled water. The grown crystals were confirmed by single crystal XRD and it is found that cadmium(II) mercury(II)-dimethyl sulfoxide belongs to the orthorhombic system with space group P212121. The FTIR studies confirmed the coordination of dimethyl sulfoxide with Cd. The UV-Vis-NIR transmission studies show the presence of a good transmission window which is the prime necessity for the material to have non-linear optical property. The non-linear optical efficiency of cadmium(II) mercury(II)-dimethyl sulfoxide crystal was studied and confirmed by Kurtz and Perry technique and compared with other well-known non-linear optical crystals. It is interesting to observe that the non-linear optical efficiency of cadmium(II) mercury(II)-dimethyl sulfoxide is superior to urea.